Impact of post‐procedural minimal stent area on 2‐year clinical outcomes in the SYNTAX II trial. Issue 4 (31st January 2019) - Katagiri, Yuki; De Maria, Giovanni Luigi; Kogame, Norihiro; Chichareon, Ply; Takahashi, Kuniaki; Chang, Chun Chin; Modolo, Rodrigo; Walsh, Simon; Sabate, Manel; Davies, Justin; Lesiak, Maciej; Moreno, Raul; et al.
Abstract: Objectives: To investigate the impact of minimal stent area (MSA) evaluated by post‐procedural intravascular ultrasound (IVUS) on clinical outcomes after contemporary PCI in patients with three‐vessel disease (TVD). Background: The impact of post‐procedural MSA on clinical outcomes has not yet been extensively studied in patients with TVD. Methods: The SYNTAX II study is a multicenter, all‐comers, open‐label, single arm study that investigated the impact of a state‐of‐the‐art PCI strategy on clinical outcomes in patients with TVD (454 patients with 1, 559 lesions). The relationships between post‐procedural MSA and lesion‐level outcomes at 2 years were investigated. Clinical events adjudicated per patient by clinical event committee were assessed per lesion. Lesion‐oriented composite endpoint (LOCE) was defined as the composite of cardiac death, target‐vessel myocardial infarction, and ischemia‐driven target lesion revascularization. Results: Eight hundred and nineteen lesions with post‐procedural MSA available in 367 patients were included in the analysis. The post‐procedural MSA per lesion was divided into terciles (smallest tercile: ≤5.0 mm 2, intermediate tercile: 5.0–6.7 mm 2, and largest tercile: >6.7 mm 2 ). LOCE was observed in 16/288 (5.6%), 15/265 (5.7%), and 8/266 (3.0%) ( P = 0.266). Target lesion revascularization (TLR) was observed in 16/288(5.6%), 12/265 (4.5%), and 4/266 (1.5%) ( P = 0.042). The multivariate analysis demonstrated that smaller post‐procedural MSA, as well as creatinine clearance, history of previous stroke, chronic total occlusion, and lesion SYNTAX Score was an independent predictor of TLR. Conclusions: In the SYNTAX II trial, larger post‐procedural MSA was independently associated with the lower rate of TLR at 2 years.